Stressed Out! Examining family meal decisions in response to daily stressors via ecological momentary assessment in a racially/ethnically diverse population - Tate, Allan (Prev Med Rep, 2020)
The impact various sources of stress have on family meal decisions and child health-related behaviors is an understudied area. For this study, 128 racially/ethnically diverse parent/child dyads were recruited from primary care clinics in the Twin Cities, Minnesota between 2015 and 2016. Parent participants completed eight days of ecological momentary assessment, which included end-of-day surveys where the parent reported on (1) sources of daily stress (e.g., family demands, work/school demands) and related family meal choices (e.g., fixed quick meal, skipped meal), (2) meal planning, and (3) parent and child health-related behaviors (e.g., watched TV, ate unhealthy snack). Adjusted generalized estimating equations were used to estimate marginal probabilities and 95% confidence intervals of outcomes by race/ethnicity. Results indicated that common meal-related choices as a result of being stressed varied from fixing a quick/easy meal, buying fast food, everyone fixing their own meal or skipping a meal, or none of the above. When parents reported family demands as the source of stress, children were three times more likely to eat an unhealthy snack. Additionally, children were more likely to eat an unhealthy snack with higher levels of parental stress or if families have not planned the meal the night before. Interventions to lower parental stress and support family meal planning may increase the healthfulness of the home food environment during moments of elevated stress.